Repetition‐dependent acute cardiopulmonary responses during intensity‐matched squats in males - Johannes Lässing; Sonja Hummelmann; Maxi Kramer; Ulrich Laufs; Sven Fikenzer; Roberto Falz (Experimental Physiology)
Abstract The ‘strength–endurance continuum’ is a key concept in strength training (ST). Although cardiopulmonary responses have seldom been reported in conjunction with ST, this repeated‐measurement study examined acute blood pressure and haemodynamic responses continuously depending on the number of repetitions but without changing the intensity. Fifteen healthy male participants (21.6 (2.0) years; mean (SD)) performed an incremental exercise test and a 3‐repetition maximum test (3‐RM) on a Smith machine. They were then randomly assigned to three ST sessions involving 10, 20 and 30 repetitions at 50% of their 3‐RM. Blood pressure (vascular unloading technique) and cardiopulmonary responses (spirometry and impedance cardiography) were continuously monitored. Heart rate (121 (10) vs. 139 (22) vs. 153 (13) bpm, P = 0.001, respectively), cardiac output (10.4 (1.9) vs. 13.6 (3.8) vs. 14.6 (3.1) L/min, P = 0.001, respectively) and diastolic blood pressure (113 (8) vs. 116 (21) vs. 135 (22) mmHg, P = 0.001, respectively) increased in the training sessions with higher repetitions. Stroke volume, systolic blood pressure and end‐diastolic volume indicated no change in peak values between training sessions. Total peripheral resistance (13.6 (2.8) vs. 11.3 (3.6) vs. 11.2 (3.1) mmHg min/L, P = 0.002, respectively) was significantly lower with 20 and 30 repetitions, while oxygen uptake (V̇O2: 15.5 (1.9) vs. 20.5 (4.1) vs. 20.6 (4.4) mL/min/kg, P = 0.001, respectively) was significantly higher. ST of moderate intensity with an exhausting number (>20) of repetitions induces strong haemodynamic responses, especially high cardiac afterload and a compensatory heart rate acceleration, which may also create a strong stimulus for cardiopulmonary adaptation.